Understanding late Holocene woodland dynamics in southwestern and western Ireland through the analysis of sub-fossil insect remains - Reilly, Eileen (Trinity College (Dublin, Ireland). Department of Botany, 2008)
The main aim of this research was to explore the validity of using sub-fossil insect remains as a proxy for reconstructing late Holocene woodland dynamics in southwestern and western Ireland. Three woodlands were examined and two types of deposit used, small hollow peat and mor humus. A prerequisite for the study was that each site had pre-existing Holocene vegetational records, derived through palynology, and documented evidence of disturbance. Chronologies for the three sites were established using a combination of tephrochronology and radiocarbon dating. A number of questions were asked of the data regarding woodland openness, climate signals and changing biodiversity. Results showed that sub-fossil insect analysis was a successful proxy for understanding forest structure during the Late Holocene, proving more discerning than pollen analysis in identifying changes at the forest floor, particularly hydrological changes and fluctuating accumulations of dead wood. Insect remains provided direct evidence of the changing biodiversity of woodlands including the loss of much of the ‘wildwood’ or Urwald elements of the insect fauna.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin